Investigations on low energy X-ray induced strong radiation-matter interaction phenomena in polymer-BiI3 hybrid materials for room temperature radiation detectors. (2022) - Chaudhari, Ritu; Kumar Sharma, Surender; Ravi Kant, Chhaya; Garg, Alka
Abstract: Investigations are reported for response of soft X-rays with applications such as X-ray crystallography and mammography, for Polymer-BiI3 (Bismuth triiodide) composite pellets at low biased voltage. The pellets were prepared with solvent free synthesis technique to avoid impurities and charge collection by electrodes has been studied with resistivity. Polymer with low resistivity showed better charge collection and has been further improved by incorporating conductive filler (MWCNT) within the composite. The results suggest that incorporation of MWCNT provide conductive channel and improves the photocurrent of the composite detector by one order.